2021
DOI: 10.4314/ahs.v21i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black tea consumption and caffeine intake on depression risk in black tea consumers

Abstract: Background: The aim of this study was to compare black tea consumption and caffeine intake with depression status. Subjects and Methods: This study was conducted on 491 adults (M:169, F:322). The average daily caffeine intake of individuals was calculated using the amounts of caffeinated beverages they consumed daily and the caffeine contents of these beverages. The participants’ depression status was determined using the Beck Depression Inventory (BDI). All of the research data were evaluated using STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Still searching for a nutritional cause for the symptoms of depression, the level of consumption of stimulants -caffeine and alcohol -was analyzed in this study. Caffeine is the most commonly used stimulant in the world and is consumed in the most significant amounts with coffee and, to a lesser extent, with black tea [63,64]. Many studies confirm the positive role of caffeine in preventing or reducing the symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still searching for a nutritional cause for the symptoms of depression, the level of consumption of stimulants -caffeine and alcohol -was analyzed in this study. Caffeine is the most commonly used stimulant in the world and is consumed in the most significant amounts with coffee and, to a lesser extent, with black tea [63,64]. Many studies confirm the positive role of caffeine in preventing or reducing the symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that consuming 4 or more cups of coffee a day significantly reduced the risk of depressive symptoms, compared to people who drank one or fewer cups of coffee a day [65]. Also, Asil et al [64] compared black tea and caffeine consumption with depression in a study conducted on 491 adults, of whom 322 were women. The average daily caffeine intake was calculated based on the volume of caffeine-containing beverages and their content in each as also used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported no significant dose-response relationship between coffee consumption and the risk of depression. Moreover, a recent study showed that black tea consumption up to four cups and a caffeine intake between 450-600 mg/day can help protect against depression [ 32 ]. In our study, the median caffeine intake was estimated to be less than that (approximately 160 mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Some have even reported that coffee or caffeine consumption increases the risk of depression, anxiety, sleep disorders and stress ( 20 , 21 ) . Several studies have shown that coffee, tea and chocolate have protective effects against depression ( 22 , 23 ) . Considering these studies, it is essential for public health to investigate the effect of consuming beverages containing high levels of caffeine, which are commonly consumed in relatively high amounts, on the psychological disorders experienced by individuals.…”
mentioning
confidence: 99%